2006
DOI: 10.1002/app.24496
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic effect of nano‐Tio2 and graphite on the tribological performance of epoxy matrix composites

Abstract: The influence of incorporated 300 nm TiO 2 (4 vol %), graphite (7 vol %), or combination of both fillers on the tribological performance of an epoxy resin was studied under various sliding load (10-40 N) and velocity conditions (0.2-3.0 m/s). Mechanical measurements indicated that the incorporation of TiO 2 significantly enhanced the flexural and impact strength of the neat epoxy and the graphite including epoxy. Tribological tests were conducted with a cylinder-on-flat testing rig. The incorporation of nano-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…A synergistic effect was found between nano-TiO 2 and graphite; this effect was ascribed to the effective transferring films on friction surfaces and the reinforcing effect of nanoparticles [26]. The lubrication of MoS 2 /TiO 2 nanoclusters can also be explained using the synergetic effect of two different additives.…”
Section: Synergetic Effect Of Nano-mos 2 and Nano-tiomentioning
confidence: 95%
See 1 more Smart Citation
“…A synergistic effect was found between nano-TiO 2 and graphite; this effect was ascribed to the effective transferring films on friction surfaces and the reinforcing effect of nanoparticles [26]. The lubrication of MoS 2 /TiO 2 nanoclusters can also be explained using the synergetic effect of two different additives.…”
Section: Synergetic Effect Of Nano-mos 2 and Nano-tiomentioning
confidence: 95%
“…TiO 2 , especially nano-TiO 2 , is a promising additive for polymers and coatings [22][23][24][25]. In addition, the synergistic lubrication effect of nano-TiO 2 and graphite in epoxy matrix composites has been studied [26].…”
Section: Introductionmentioning
confidence: 99%
“…The TiO 2 is extensively used in industry, such as additives for epoxies, plastics, and rubbers [6,[26][27][28][29][30]. Moreover, TiO 2 filled polymers are well-known antimicrobial materials [31][32][33][34][35].…”
Section: Journal Of Polymersmentioning
confidence: 99%
“…Shie showed that both wear rate and the coefficient of friction (COF) were reduced. Xian et al reported that a synergistic effect was found for the combination of nano‐TiO 2 and graphite on the tribological performance of the epoxy matrix composites, which led to the lowest COF and wear rate. Suresha and coworkers demonstrated that the lowest wear rate was obtained with nanoclay and SCF fillers.…”
Section: Introductionmentioning
confidence: 99%